2022
DOI: 10.1007/s00167-022-07167-0
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic-assisted locking block modified Krackow technique combined with a V-Y flap for chronic Achilles tendon rupture

Abstract: PurposeThe purpose of this study was to evaluate the clinical outcomes of the endoscopic‐assisted locking block modified Krackow technique with a V‐Y flap. The hypothesis was that the minimally invasive technique can reduce wound complications and facilitate early recovery. MethodsIn total, 29 men with chronic Achilles tendon rupture who underwent either minimally invasive technique (n = 13) or open repair (n = 16) at our department between 2013 and 2019 were retrospectively analyzed. The rate of complications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…A recent animal study showed that the absence of the paratenon results in delayed formation of the tendon callus, decreased blood supply and a biomechanically weaker tendon [26]. It has been stated that even long incisions applied in open repair may impair tendon healing by decreasing blood supply [38]. An increase in the length of the tendon following acute ATR can affect various factors, including reduced tendon tension and heel-rise height, increased pennation angle, shorter fascicle length and weakness in plantar flexor power and pushoff mechanism [2,9,16,17,28].…”
Section: Discussionmentioning
confidence: 99%
“…A recent animal study showed that the absence of the paratenon results in delayed formation of the tendon callus, decreased blood supply and a biomechanically weaker tendon [26]. It has been stated that even long incisions applied in open repair may impair tendon healing by decreasing blood supply [38]. An increase in the length of the tendon following acute ATR can affect various factors, including reduced tendon tension and heel-rise height, increased pennation angle, shorter fascicle length and weakness in plantar flexor power and pushoff mechanism [2,9,16,17,28].…”
Section: Discussionmentioning
confidence: 99%
“…However, studies focusing on the surgical management of CATR were reviewed, specifically those with evidence levels A to D. The researchers carefully analyzed the inclusion criteria of the identified studies to observe and determine the surgical indications for CATR. Following the above search strategy, 16 studies were included [33,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70], of which 1 study was grade A [56], 1 study was grade B [57], 6 studies were grade C [33,[58][59][60][61][62], and 8 studies were grade D [63][64][65][66][67][68][69][70]. The most common conditions for which surgical management is indicated were CATR patients exhibiting signs of functional limitation, such as pain or tenderness, inability to execute a single heel raise, or repetitive single-leg heel raise endurance exercises, as well as difficulty in walking and ascending stairs, along with ankle swelling; these symptoms were accompanied by positive results in the call squeeze and knee flexion [71], and their diagnoses were confirmed through MRI or ultrasound examinations (16 studies).…”
Section: What Are the Indications For Surgical Treatment Of Catr?mentioning
confidence: 99%